(untitled) (Bangladesh Journal of Urology, 2022)
Purpose: Urinary stone disease is a systemic metabolic and recurrent disease. It is the third most common disease of the urinary tract. Urolithiasis affects 4%-15% of the world population and this is increasing. Treatment of urinary stone disease moved dramatically from open operative procedures to endoscopic, minimally invasive, and noninvasive methods. The introduction of shock wave lithotripsy (SWL) has revolutionized the treatment of urinary stones with the concept of disintegration of stones. The present study aims to evaluate the outcome of SWL in the treatment of urinary stone disease. Methods and Materials: This retrospective observational study was conducted in the department of urology, SOMCH from June 2019- to March 2021. Renal stone <2.0 cm & upper Ureteric stone <1.5 cm were included and radiolucent stones, patients having ureteral obstruction with grossly impaired renal function, UTI, uncontrolled bleeding disorder, pregnancy & BMI >30kg/m2 were excluded. A total of 115 patients was enrolled. SWL with Siemens Lithoskope (3rd generation) lithotripter was used with a standard number of shock waves 2500-3500 per session & an energy setting of 3.0-3.5 KV. NSAID was given in suppository form and intravenous pethidine just before starting shock for analgesia and all were under antibiotic prophylaxis. Patients were discharged the day after the SWL procedure with the advice of follow-up every 2 weeks for 3 months. All patients were followed up with history, urine R/M/E & C/S to detect UTI, plain X-ray KUB region to see stone clearance or any other complications. Results: Total 179 sessions of SWL procedure done for 115 patients (1.55/ patient) with the urinary stone of both gender between 19 to 70 years. Of them, 82(71.3%) were male and 33(28.7%) female and 94(81.5%) were in the 20-60 years age group. Renal stones 78(67.9%), upper ureteric stones 37(32.1%), and 70(60.8%) were on the left side. Preprocedure stenting was done in 35(30.4%) patients due to obstruction & residual stones. 70(60.9%) have achieved stone clearance after the first session of SWL. After a maximum of 3 sessions of SWL and 3 months follow up found that 99(86%) patients were stone-free. Only 16(14%) found treatment failure and needed auxiliary procedures like URS, RIRS, etc because of hard stone, steinstrasse, and patients’ non-compliance due to pain & fearlessness. 13(11.3%) patients complain of moderate pain after SWL and needed a maximum of 2 days of hospitalization with an injectable pain killer. UTI was found in 9(7.8%) patients, of the 7(6.1%) were pre-stenting. Gross hematuria was found in 2(1.7%) patients due to HDN & UTI. Conclusion: As the stone clearance rate is high with fewer complications however multiple sessions are required, SWL, a noninvasive procedure, is a good option for the treatment of urinary stone disease. Bangladesh J. Urol. 2021; 24(2): 166-169